Balloon dilation of the esophago‐gastric junction affects lower and upper esophageal sphincter function in achalasia. Issue 1 (4th September 2013) - Wauters, L.; Van, L.; Selleslagh, M.; Vanuytsel, T.; Boeckxstaens, G.; Tack, J.; Omari, T.; Rommel, N.
Abstract Background Pneumatic dilation of the lower esophageal sphincter (LES) in achalasia has an unappreciated effect on upper esophageal sphincter (UES) function. We studied UES pressure patterns at baseline and alterations in UES parameters resulting from therapy. Methods High‐resolution manometry (HRM) tracings from 50 achalasia patients, seen at a tertiary center between January 2009 and July 2011, were reviewed. Manometric parameters studied were (i) LES: resting pressure (restP), 4‐second integrated relaxation pressure (IRP4); (ii) UES: resting pressure (restP), minimal relaxation pressure (MRP), peak pressure (PP), relaxation interval (RI), intrabolus pressure (IBP), and deglutitive sphincter resistance (DSR). Mixed models analyses with LES and UES parameters as dependent variables and treatment stage as within‐subject independent variable of interest were used. Correlations between treatment‐induced changes in LES, UES, and esophageal body (EB) parameters were performed. Key Results Pre‐ and posttreatment HRM tracings were available from 50 patients (mean age 52.7 ± 18.6 years, 29 men). Upper esophageal sphincter parameters MRP (17.9 ± 1.2 vs 15.2 ± 0.9 mmHg; p = 0.02) and IBP (31.5 ± 1.5 vs 27.4 ± 1.2 mmHg; p = 0.009) were significantly reduced after initial balloon dilation and this effect was significant in type II achalasia (p = 0.002 and p = 0.0006). Peak pressure, RI, and DSR were not. The therapeutic effect on LES IRP4 correlated significantly with the change in UES MRP, statistically mediated by the change in EB deglutitive pressure (p = 0.004 and p = 0.0002). Conclusions & Inferences We present the first HRM study demonstrating that pneumatic dilation of the LES affects intraesophageal and UES pressures in patients with achalasia.